The Influence of the Central Electrode Material on Coaxial Magnetic Plasma Accelerator Operation; Applied Mechanics and Materials; Vol. 698 - Pak A. Ya. Aleksandr Yakovlevich; Shanenkov I. I. Ivan Igorevich; Shatrova K.; Sivkov A. A. Aleksandr Anatolyevich (2014, 2014)
Materials based on carbon and nitrogen, and tungsten carbides exhibit catalytic properties that allow implementing the production of hydrogen from water. These materials can be prepared by various techniques, including the method of plasma dynamic synthesis in the electro-discharge plasma jet generated by a coaxial magnetic plasma accelerator. The device is experimental and requires further research and modification. The paper presents obtained operating parameters of the coaxial magnetic plasma accelerator in dependence on the material from which the central electrode is made